Older adult education in two universities: A comparison in the New Zealand and Scottish contexts. Issue 1 (May 2016) - Findsen, Brian; Mark, Rob
This article examines the character of older adult education provision in two universities at opposite ends of the globe. The universities of Waikato (New Zealand) and Strathclyde (Scotland) are analysed in terms of specific domains: funding, curriculum and provision, older people's participation and university–community relationships. These two universities' work in these areas is contextualised in the wider framework of prevailing societal trends, lifelong learning discourses, higher education, and adult and community education. While both institutions have much in common from the perspective of a British influence, there are significant differences across the four domains as both universities contest the right to engage with older adults' learning in a neoliberal environment.